Structural and Quantitative Analysis of Polyfluoroalkyl Substances (PFASs) and Para-Phenylenediamines (PPDs) by Direct Analysis in Real Time Ion Mobility Mass Spectrometry (DART-IM-MS) - Calum Bochenek; Jack Edwards; Zhibo Liu; Chrys Wesdemiotis (Molecules, 2025)
Polyfluoroalkyl substances (PFASs) and para-phenylenediamines (PPDs) are emerging classes of anthropogenic contaminants that are environmentally persistent (most often found in ground and surface water sources), bioaccumulative, and harmful to human health. These chemicals are currently regulated in the US by the Environmental Protection Agency (EPA), the Food and Drug Administration (FDA), and the Occupational Safety and Health Administration (OSHA). Analysis of these contaminants is currently spearheaded by mass spectrometry (MS) coupled to liquid chromatography (LC) because of their high sensitivity and separation capabilities. Although effective, a major flaw in LC-MS analysis is its large consumption of solvents and the amount of time required for each experiment. Direct analysis in real time mass spectrometry (DART-MS) is a new technique that offers high sensitivity and permits rapid analysis with little to no sample preparation. Herein, we present the qualitative and quantitative analysis of PFASs and PPDs by high-resolution DART-MS, interfaced with ion mobility (IM) and tandem mass spectrometry (MS/MS) characterization, demonstrating the utility of this multidimensional approach for the fast separation and detection of environmental contaminants.